Corrupt language, corrupt thought: the White Paper The importance of teaching. (15th May 2013) - Lumby, Jacky; Muijs, Daniel
<x xml:space="preserve">Abstract</x> This article deconstructs the language of the 2010 UK Coalition Government's White Paper, The Importance of Teaching. It uses analytical frameworks related to rhetoric established by Aristotle and Cicero. It explores the mechanisms of language using both critical discourse analysis and content analysis, offering quantitative data on the content of the paper and qualitative data on the literary strategies employed. It is concerned not only with how what is communicated persuades but also the ethics of persuasion; what is suggested and to what end. The article suggests a mutually reinforcing relationship between poverty of language and poverty of thought. The Coalition Government asserts an heroic stance to act radically to free victimised teachers from the burdens of bureaucracy imposed by the previous government. However, rather than radical action to make change, the findings suggest that the White Paper presents an illusory carapace of change that conceals fundamental continuity. It reassures all of the commitment of government and audiences to change while sustaining education as fundamentally unchanged.